P090 Risk of Rectal Cancer after Colectomy in Patients with Inflammatory Bowel Disease – A Nationwide Population-based Danish Cohort Study 1978–2018. (27th May 2021) - Akimenko, E; Bjerrum, J T; Allin, K H; Iversen, A T; Jess, T
Abstract: Background: The risk of surgery remains high both among patients with ulcerative colitis (UC) and patients with Crohn's disease (CD) with a cumulative risk of subtotal colectomy with ileostomy and diverted rectum of 7.5% after 5 years in UC and a similar risk in CD. Ileostomy with diverted rectum after colectomy may be permanent, or the patient can undergo restorative surgery with ileo-rectal anastomosis (IRA) or ileal pouch-anal anastomosis (IPAA). Risk of rectal cancer in this patient population remains uncertain. We performed a nationwide population-based Danish study of rectal cancer (RC) risk after subtotal colectomy. Methods: Through the Danish Civil Registration System, a source population of all individuals 15 years or older living in Denmark between 1978 and 2018 was retrieved. By use of the unique personal identification number given to all citizens at birth, this source population was linked to the Danish National Patient Registry (NPR) in order to identify all patients with inflammatory bowel disease (IBD). Patients with a diverted rectum, IRA or IPPA after colectomy were also identified with NPR. Cases of RC were identified in the Danish Cancer Registry. Patients with IBD were followed from the date of surgery until cancer, emigration, death or end of the study. The risk of RC in patients with diverted rectum was assessed using Cox regression analyses, as compared to the background population as well as to subjects with IBD without subtotal colectomy. Results: RC occurred in 42 (0.9%) of 4931 patients after subtotal colectomy with diverted rectum, compared to 209 (0.4%) of 49, 251 in the matched IBD cohort with no colectomy and 941 (0.4%) of 246, 550 in the matched background population. In the IBD and subtotal colectomy population 11 (26%) of the 42 cases were in patients diagnosed with CD and 31 (74%) were in patients with UC. The hazard ratio (HR) for RC in IBD patients with diverted rectum vs. matched IBD patients without colectomy (adjusted for IBD type and sex) was 0.80 (95% CI 0.29, 2.17) during the first 10 years of follow-up and 7.93 (95% CI 5.48, 11.48) 10 years or more after colectomy. Likewise, the HR for RC in IBD patients with diverted rectum compared to the matched background population was 0.85 (95% CI 0.32, 2.28) during the first 10 years of follow-up and 10.25 (95% CI 7.36, 14.28) 10 years or more after colectomy. Conclusion: In our nationwide population-based cohort study covering years 1978–2018 we observed an 8 to 10-fold increased risk of RC of the diverted rectum 10 years after colectomy.These data suggest a need for developing a specific surveillance strategy for this group of IBD patients.